2021
DOI: 10.1039/d1cs00722j
|View full text |Cite
|
Sign up to set email alerts
|

Directed genome evolution driven by structural rearrangement techniques

Abstract: This review provides insight into the emerging field of directed genome evolution driven by structural rearrangement techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…Although studies of ring chromosomes have been reported, chromosome circularization resulting from SCRaMbLE has not been reported in previous studies. ,,, To investigate whether chromosome circularization has an impact on the intrachromosomal interactions of the synthetic chromosome and the interchromosomal interactions for globular configurations, we applied Hi-C, a genome-wide version of the chromosome conformation capture (3C) technique, to test the three-dimensional (3D) organization of the circular synV strain yML100. Previous studies of the 3D organization of synthetic yeast chromosomes have revealed that the global genomic organization is unaffected and that SCRaMbLE events, including simple deletions, inversions, duplications, and translocations, can be detected by contact maps . Here, the Hi-C contact map (representing intrachromosomal contact frequencies for a single chromosome) of synV in strain yML100 showed the absence of a signal at both chromosome ends, which indicated that both ends of synV had been deleted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies of ring chromosomes have been reported, chromosome circularization resulting from SCRaMbLE has not been reported in previous studies. ,,, To investigate whether chromosome circularization has an impact on the intrachromosomal interactions of the synthetic chromosome and the interchromosomal interactions for globular configurations, we applied Hi-C, a genome-wide version of the chromosome conformation capture (3C) technique, to test the three-dimensional (3D) organization of the circular synV strain yML100. Previous studies of the 3D organization of synthetic yeast chromosomes have revealed that the global genomic organization is unaffected and that SCRaMbLE events, including simple deletions, inversions, duplications, and translocations, can be detected by contact maps . Here, the Hi-C contact map (representing intrachromosomal contact frequencies for a single chromosome) of synV in strain yML100 showed the absence of a signal at both chromosome ends, which indicated that both ends of synV had been deleted.…”
Section: Resultsmentioning
confidence: 99%
“…Here, in contrast to the traditional strategy of using wild-type yeasts, synthetic Saccharomyces cerevisiae, which contains synthetic chromosomes, was used. Several characteristics of the synthetic yeast chromosomes helped us to study the structural variations and adaptations of yeast chromosome ends. First, an inducible recombination system, SCRaMbLE (synthetic chromosome rearrangement and modification by LoxPsym-mediated evolution), was introduced into the synthetic chromosomes. Hundreds of loxPsym sites are distributed on synthetic chromosomes. Induction of Cre recombinase expression can trigger site-specific recombination of these loxPsym sites and generate structural variations, including deletions, inversions, duplications, and translocations. When these structural variations involve chromosome ends, a large number of materials can be generated to study variations and adaptations of chromosome ends.…”
Section: Introductionmentioning
confidence: 99%
“…And the handbook of personalized therapies for AR-mutated PCa patients is still missing. Synthetic biology in yeast offers a solution to this problem, as yeast can be easily customized to realize various purposes [ [26] , [27] , [28] , [29] , [30] , [31] , [32] ] [ [26] , [27] , [28] , [29] , [30] , [31] , [32] ] [ [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. Yeast Two-Hybrid (Y2H) is commonly used to study binary protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by natural selection, this engineering approach encompasses cycles of genetic diversification and enrichment of rare desired variants, allowing for accelerated protein evolution even with limited a priori knowledge about the structure-function relationships (Romero and Arnold, 2009; Packer and Liu, 2015; Wang et al, 2021). Directed evolution enabled engineering of a plethora of proteins, genetic pathways, and even genomes to generate variants with improved or tailor-made properties (Chatterjee and Yuan, 2006; Johannes and Zhao, 2006; Hida et al, 2007; Turner, 2009; Xiong et al, 2012; Bornscheuer et al, 2019; Engqvist and Rabe, 2019; Zhou et al, 2021). Incorporation of directed evolution principles to the construction framework of a synthetic cell has recently been proposed (Abil and Danelon, 2020).…”
Section: Introductionmentioning
confidence: 99%